Comparison of Gait Parameters Across Three Attentional Loading Conditions During Timed Up and Go Test in Stroke Survivors. Issue 2 (March 2014) - Manaf, Haidzir; Justine, Maria; Hui Ting, Goh; Abd Latiff, Lydia
Abstract : Background: Little is known about the effects of attentional loading on performance of turning during walking in individuals with stroke.Objective: The authors used a cross-sectional experimental design to compare gait parameters in stroke survivors across 3 attentional loading conditions (single, dual-motor, and dual-cognitive conditions) during a Timed Up and Go (TUG) test.Methods: Data were collected from 20 stroke survivors (12 males, 8 females; mean age, 60.5 ± 10.6 years). We compared the number of steps and time measured during the TUG test under 3 attentional loading conditions and 2 turning directions (nonparetic and paretic sides). We further divided the TUG test into straight walking and turning phases.Results: The number of steps and the time taken during TUG test increased significantly from single- to dual-task conditions (dual motor and dual cognitive). However, there were no significant differences in gait parameters between turning toward the nonparetic and paretic sides.Conclusions: These findings suggested that gait performance was compromised during dual-task conditions for individuals with stroke. Attentional loading may be incorporated into routine gait assessment and rehabilitation to ensure a successful recovery.